First ruthenium organometallic complex of antibacterial agent ofloxacin. Crystal structure and interactions with DNA - Turel, Iztok (2010)
Organometallic ruthenium complex of quinolone antibacterial agent ofloxacin [(η(6)-p-cymene)RuCl(O,O-oflo)]·2.8H(2)O (1·2.8H(2)O) was isolated and its crystal structure was determined. In this »piano-stool« complex, quinolone is bidentately coordinated to the metal through the ring carbonyl and one of the carboxylic oxygen atoms. Interactions of the title complex with DNA were studied by spectroscopic methods (electronic, fluorescence, CD) and atomic force microscopy (AFM). It was established that the electrostatic attraction between the ruthenium complex and DNA in a solution is important for the binding since interactions were observed only in a solution with low ionic strengths. An induced CD (ICD) signal was observed in the solution of DNA and title complex which proves the interaction between ruthenium and macromolecule. Competitive binding between cisplatin and 1 to DNA revealed that cisplatin prevents binding of 1. Our experiments revealed that binding of the title complex to DNA occurs also if guanine N7 is protonated. AFM has shown that title complex provokes DNA shrinkage. Preliminary biological tests have also been performed.